Development of functionalized carrageenan, chitosan and alginate as polymeric chelating ligands for water softening - Ali, K.; Hassan, M.; Elnashar, Magdy (Center for Environmental and Energy Research and Studies, 2017)
Chitosan, carrageenan and alginate are among the most abundant biopolymers in nature. They were prepared in uniform beads shape with a diameter of 2 mm ± 10%, using the encapsulator for removal of calcium, magnesium and iron cations from hard water. Solutions of 100–500 mg/L were prepared from each cation, and the detection of cations was carried out using atomic absorption spectrometer. Carrageenan and chitosan were able to chelate the three cations without further modification. However, alginate beads succeeded to chelate iron and magnesium and failed to chelate any calcium ions; in contrast, it increased the initial calcium concentration! That could be due to the pre-cross-linking of alginate beads using calcium chloride solution, which may be leaked back to the solution. However, grafting the alginate beads with polyethyleneimine and bromoacetic acid rectified this problem and the new functional group, –COOH, has been proved using the FT-IR. Optimization of the results in terms of beads weight (0.25–3.0 g) and cations concentrations (100–500 mg/L) has shown that most biopolymeric beads can chelate 85–100% of the cations in concentrations up to 500 mg/L. According to our finding, we came up with the recommendation to use chitosan for chelation of calcium and iron as it showed 100% chelation efficiency of both cations, whereas carrageenan is highly recommended for chelation of iron and magnesium, as it showed 100 and 98% chelation efficiency, respectively. Further work can be done on the reusability of the beads and scale up for the industrial use.